Real-world cardiovascular disease burden in patients with atherosclerotic cardiovascular disease: a comprehensive systematic literature review. (4th March 2018) - Cherepanov, Dasha; Bentley, Tanya G.K.; Hsiao, Wendy; Xiang, Pin; O'Neill, Frank; Qian, Yi; Yurgin, Nicole; Beenhouwer, David
Abstract: Objective: Based on randomized controlled trials (RCTs), non-fatal myocardial infarction (MI) rates range between 9 and 15 events per 1000 person-years, ischemic stroke between 4 and 6 per 1000 person-years, CHD death rates between 5 and 7 events per 1000 person-years, and any major vascular event between 28 and 53 per 1000 person-years in patients with atherosclerotic cardiovascular disease (ASCVD). We reviewed global literature on the topic to determine whether the real-world burden of secondary major adverse cardiovascular events (MACEs) is higher among ASCVD patients. Methods: We searched PubMed and Embase using MeSH/keywords including cardiovascular disease, secondary prevention and observational studies. Studies published in the last 5 years, in English, with ≥50 subjects with elevated low-density lipoprotein cholesterol (LDL-C) or on statins, and reporting secondary MACEs were included. The Newcastle–Ottawa Scale (NOS) was used to assess the quality of each included study. Results: Of 4663 identified articles, 14 studies that reported MACE incidence rates per 1000 person-years were included in the review (NOS grades ranged from 8 to 9; 2 were prospective and 12 were retrospective studies). Reported incidence rates per 1000 person-years had a range (median) of 12.01–39.9 (26.8) for MI, 13.8–57.2 (41.5) for ischemic stroke, 1.0–94.5 (21.1) for CV-related mortality and 9.7–486 (52.6) for all-cause mortality. Rates were 25.8–211 (81.1) for composite of MACEs. Multiple event rates had a range (median) of 60–391 (183) events per 1000 person-years. Conclusions: Our review indicates that MACE rates observed in real-world studies are substantially higher than those reported in RCTs, suggesting that the secondary MACE burden and potential benefits of effective CVD management in ASCVD patients may be underestimated if real-world data are not taken into consideration.